2015
DOI: 10.1016/j.metabol.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The association between N-terminal pro B-type natriuretic peptide and lipoprotein particle concentration plateaus at higher N-terminal pro B-type natriuretic peptide values: Multi-Ethnic Study on Atherosclerosis

Abstract: Background The association between N-terminal pro B-type natriuretic peptide (NT-proBNP) and blood levels of small and large LDL- and HDL- particle (P) concentration may not be linear throughout the whole range of NT-proBNP values. Methods Linear spline regression analysis between NT-proBNP and lipoprotein particle concentrations was performed cross-sectionally in 5597 individuals from the Multi-Ethnic Study of Atherosclerosis adjusted for age, race, sex, body mass index, % of energy from saturated fats, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…NT-proBNP and BNP levels are inversely correlated with BMI in the general population and obese individuals have typically lower BNP concentrations independent of cardiovascular disease (CVD) [ 9 , 10 ]. A recent study further revealed that BNP within the reference range (< 100 ng/L) was inversely correlated with total cholesterol, non-HDL cholesterol, and non-fasting triglycerides representing a favorable lipoprotein profile confirming an observation from a number of previous studies [ 11 13 ]. In contrast, in CVD—for which dyslipidemia is a well-known risk factor [ 14 ]—NT-proBNP or BNP levels are typically elevated.…”
Section: Introductionsupporting
confidence: 77%
“…NT-proBNP and BNP levels are inversely correlated with BMI in the general population and obese individuals have typically lower BNP concentrations independent of cardiovascular disease (CVD) [ 9 , 10 ]. A recent study further revealed that BNP within the reference range (< 100 ng/L) was inversely correlated with total cholesterol, non-HDL cholesterol, and non-fasting triglycerides representing a favorable lipoprotein profile confirming an observation from a number of previous studies [ 11 13 ]. In contrast, in CVD—for which dyslipidemia is a well-known risk factor [ 14 ]—NT-proBNP or BNP levels are typically elevated.…”
Section: Introductionsupporting
confidence: 77%
“…33 Comparison of the upper versus the lowest three sextiles of baseline NT-proBNP was associated with a 32% lower adjusted risk of this outcome, but attenuation of the association occurred at levels toward the upper limit of the fifth sextile (>150 pg/ml), 33 consistent with similar flattening of NT-proBNP’s associations with metabolic risk factors as concentrations reached a higher range. 11, 12 The same study 33 reported a U-shaped association for subsequent 3-year interval change in NT-proBNP and diabetes. Taken together with the ARIC results, these findings are consistent with the adverse metabolic impact of pathologic elevations of NT-proBNP into the higher range, as compared with physiologic elevations.…”
Section: 0 Discussionmentioning
confidence: 90%
“…NP receptors are expressed in adipose tissue and skeletal muscle, and NPs have been shown to promote adipocyte browning, foster adipokine secretion and increase oxidative capacity in muscle. 38 In clinical studies, higher levels of N-terminal proBNP (NT-proBNP), a cleavage product of proBNP, are associated with less obesity and metabolic syndrome, 912 and a decreased risk of incident type 2 diabetes. 1316 Moreover, studies of genetic variants in the natriuretic peptide precursor A ( NPPA ) and B ( NPPB ) loci suggest that mild, lifelong elevations in natriuretic peptides may protect against type 2 diabetes.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Obesity is associated with cardiovascular diseases; however, BNP and NT-proBNP levels are paradoxically reduced in obese subjects and a negative linear relationship between body mass index (BMI) and both BNP and NT-proBNP levels has been consistently reported in epidemiological studies [ 7 9 ]. Recently, this inverse association has been also confirmed in morbid obese subjects [ 10 ].…”
Section: Introductionmentioning
confidence: 99%